Composite carrier roller and preparation method thereof
By using composite rollers with quartz sand, polypropylene, graphite and other components and adding wear-resistant additives and flame retardants, the problems of insufficient service life and wear resistance in harsh environments are solved, and the existing rollers are not used for a long time and insufficient wear resistance in harsh environments are achieved. Higher wear and impact resistance and extend service life.
Patent Information
- Application Number
- CN202510038380.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The existing composite rollers have little service life in harsh environments and lack wear resistance, making it difficult to meet the efficient operation needs of industrial conveyor belt systems.
The roller roller body is prepared using quartz sand, polypropylene, graphite and other components, and the wear-resistant additive and flame retardant are added during the preparation process. The components are fully mixed and pretreated through fluidized bed spraying technology to improve the support The wear and corrosion resistance of the roller.
It significantly improves the wear resistance of composite rollers in complex environments, extending their service life to more than 5 times that of ordinary steel rollers and more than 2-3 times that of ordinary non-metal rollers, while enhancing impact resistance and Corrosion resistance.
Smart Images

Figure CN119429503A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of conveying equipment, and in particular, to a composite roller and a preparation method thereof. Background Art
[0002] Belt conveyor is the basic form of modern industrial material transportation, and is widely used in mining, metallurgy, ports, thermal power, cement and building materials industries. In coal mines and other working scenarios, it is usually necessary to transport materials such as coal slag and soil from underground to a designated location through a conveyor belt. For details, please refer to the Chinese invention patent application CN118850626A. As an important consumable component in the conveyor belt system, the life and performance of the roller have a huge impact on the conveying efficiency and cost.
[0003] Compared with traditional metal rollers, composite rollers made of non-metallic materials have advantages in anti-deformation, anti-static, anti-magnetic, wear resistance and service life, but there is still room for improvement.
[0004] In view of this, this application is filed. Summary of the invention
[0005] The purpose of the present application is to provide a composite roller and a preparation method thereof to solve at least one technical problem mentioned in the background technology.
[0006] Specifically, in a first aspect of the present application, a composite roller is provided, comprising: The connecting shaft has two ends connected to the mounting plate. The bearing seat is mounted on both ends of the connecting shaft. A bearing is disposed in the bearing seat and is capable of rotating relative to the connecting shaft. The sealing structure is arranged in the bearing seat and seals the bearing. The roller body is sleeved on the outside of the bearing upper seat, and its surface is in contact with the conveyor belt, and is used to support the conveyor belt; Wherein, the roller body comprises the following components: 6-20 parts of quartz sand, Polypropylene 5-10 parts, 1-3 parts of graphite.
[0007] By adopting the above technical solution, by setting the components of the roller body to quartz sand, polypropylene, and graphite, the wear resistance of the composite roller in complex environments can be improved, making the quality of the composite roller significantly better than that of the prior art in specific environments.
[0008] Preferably, the roller body further includes:
[0009] Carbon black 0.5-2 parts.
[0010] Preferably, the roller body further includes: Wear-resistant additive 0.08-0.5 parts, The wear-resistant additives include: The mass ratio of polytetrafluoroethylene, stearic acid and sodium carboxymethyl cellulose is 5-8:1-2:1.
[0011] Preferably, the preparation method of the wear-resistant additive comprises the steps of: Take the indicated amount of sodium carboxymethyl cellulose and dissolve it in an appropriate amount of warm water, the temperature of which is 30-50°C, to obtain a sodium carboxymethyl cellulose solution. Take polytetrafluoroethylene and stearic acid and place them in a fluidized bed. The sodium carboxymethyl cellulose solution is sprayed to achieve material mixing in a fluidized bed; wherein the flow rate of the sodium carboxymethyl cellulose solution is 5-20 L / h, the air inlet temperature of the fluidized bed is 45-55°C, and the air inlet volume is 10-20 m 3 / h, atomization pressure is 0.5-1.5Bar; After spraying, the particles are dried at 40-55°C for 10-40 minutes to obtain composite A particles.
[0012] Preferably, the composite A with a particle size of 200-500 μm is screened as the wear-resistant additive.
[0013] Preferably, polytetrafluoroethylene and stearic acid are taken, passed through a 16-mesh sieve, and placed in a fluidized bed.
[0014] Preferably, the roller body further includes: Flame retardant 0.2-2 parts, The flame retardant is selected from boron flame retardant or phosphorus flame retardant.
[0015] Preferably, the boron flame retardant is zinc borate, and the phosphorus flame retardant is aluminum hypophosphite.
[0016] Preferably, the roller body further includes: Lubricant 0.05-0.2 parts, The lubricant is selected from paraffin or molybdenum disulfide.
[0017] Preferably, the roller body further includes: Polyethylene glycol 8000 0.01-0.1 parts.
[0018] Preferably, the roller body does not contain silicon dioxide, or more preferably, the silicon dioxide content in the roller body is not higher than 0.01 parts or the mass ratio is not higher than 0.012%.
[0019] A second aspect of the present application provides a method for preparing a composite roller, comprising the steps of: Prepare the raw materials for the rollers, Preparation of roller bodies, Assemble and form, The step of preparing the roller body specifically includes: Stir the raw materials. Put the prepared raw materials into the blender and stir for 10-60 minutes. Raw material extrusion, the components obtained in the raw material stirring step are placed into the extruder, heated at 100-240°C for 10-30 minutes, Compression molding: placing the components obtained in the raw material extrusion step into a compression mold of a compression machine for compression molding.
[0020] Preferably, the preparation of the raw material for the roller comprises the steps of: The raw materials were sieved to make the particle size no greater than 500 μm.
[0021] Preferably, the extruder comprises a feed inlet heating section, a feed zone heating section, a screw zone heating section, a barrel zone heating section and a die head heating section, and the heating temperatures are 100-120°C, 120-160°C, 160-200°C, 200-240°C, 240-180°C, and the heating times are 2-5min, 2-5min, 2-10min, 2-5min, 2-5min, respectively.
[0022] Preferably, the roller body further includes: Wear-resistant additive 0.08-0.5 parts, The wear-resistant additives include: The mass ratio of polytetrafluoroethylene, stearic acid and sodium carboxymethyl cellulose is 5-8:1-2:1.
[0023] Preferably, the preparation method of the wear-resistant additive comprises the steps of: Take the indicated amount of sodium carboxymethyl cellulose and dissolve it in an appropriate amount of warm water, the temperature of which is 30-50°C, to obtain a sodium carboxymethyl cellulose solution. Take polytetrafluoroethylene and stearic acid and place them in a fluidized bed. The sodium carboxymethyl cellulose solution is sprayed to achieve material mixing in a fluidized bed; wherein the flow rate of the sodium carboxymethyl cellulose solution is 5-20 L / h, the air inlet temperature of the fluidized bed is 45-55°C, and the air inlet volume is 10-20 m 3 / h, atomization pressure is 0.5-1.5Bar; After spraying, the particles are dried at 40-55°C for 10-40 minutes to obtain composite A particles.
[0024] Preferably, the composite A with a particle size of 200-500 μm is screened as the wear-resistant additive.
[0025] Preferably, polytetrafluoroethylene and stearic acid are taken, passed through a 16-mesh sieve, and placed in a fluidized bed.
[0026] In summary, this application has the following beneficial effects: First, the composite roller provided in the present application can improve the wear resistance of the composite roller in complex environments by setting the components of the roller body to quartz sand, polypropylene, and graphite, so that the quality of the composite roller in specific environments is significantly better than that of the prior art.
[0027] Second, the composite roller provided in the present application can further improve the wear resistance of the composite roller in a specific environment by providing a wear-resistant additive of a specific component, thereby extending its working life and thereby improving the conveying efficiency of the conveyor belt; under the same industrial and mining conditions, the service life of the composite roller provided in the present application is more than 5 times that of ordinary steel rollers and more than 2-3 times that of ordinary non-metallic rollers; at the same time, in a complex working environment, it is more corrosion-resistant than metal materials.
[0028] Third, the preparation method of the composite roller provided in the present application has a simple process, can make the raw materials quickly molded, has reliable quality, is lighter in weight, is 1 / 3 the weight of a steel roller, is easy to install and maintain, can significantly reduce the labor intensity of workers, and has good commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 This is a schematic diagram of the structure of the antistatic ability testing equipment in this application; Figure 2 This is a working principle diagram of the antistatic ability testing equipment in this application; Figure 3 This is a schematic diagram of the structure of the composite roller in some embodiments of the present application.
[0031] Marking description: Through the above-mentioned figure marking description, combined with the embodiments of the present application, the technical solution of the present application can be more clearly understood and explained.
[0032] 10. Connecting shaft; 20. Bearing seat; 30. Bearing; 40. Sealing structure; 50. Roller body. DETAILED DESCRIPTION
[0033] Exemplary embodiments will be described in detail herein, examples of which are shown in the accompanying drawings. When the following description refers to the drawings, the same numbers in different drawings represent the same or similar elements unless otherwise indicated. The implementations described in the following exemplary embodiments do not represent all implementations consistent with the present application. Instead, they are merely examples of devices and methods consistent with some aspects of the present application as detailed in the appended claims.
[0034] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.
[0035] The present application will be described in detail below through examples.
[0036] In the existing technology, belt conveyor is the basic form of modern industrial material transportation, and is widely used in mining, metallurgy, ports, thermal power, cement and building materials and other industries. Specifically in coal mines and other working scenarios, it is usually necessary to transport materials such as coal slag and soil from underground to designated locations through conveyor belts. As important consumable parts in the conveyor belt system, the life and performance of rollers have a huge impact on the conveying efficiency and cost. Compared with traditional metal rollers, composite rollers made of non-metallic materials have advantages in anti-deformation, anti-static, anti-magnetic, wear resistance, and service life. However, in some specific harsh environments such as wet flue gas desulfurization, the service life of non-metallic composite rollers is still unsatisfactory.
[0037] In view of this, in order to solve the existing technical problems in the background technology, the inventive concept of the present application is to provide a composite roller and a preparation method thereof, wherein the composite roller is applied to a conveyor belt system, comprising: a connecting shaft, both ends of which are respectively fixed to a mounting plate; a bearing seat, sleeved on both ends of the connecting shaft; a bearing, sleeved on the bearing seat; a roller body, sleeved on the bearing, a surface of which is in contact with a conveyor belt, and is used to support the conveyor belt; wherein the roller body comprises the following components: 6-20 parts of quartz sand, 5-10 parts of polypropylene, and 1-3 parts of graphite.
[0038] According to the inventive concept, by setting the components of the roller body to quartz sand, polypropylene, and graphite, the wear resistance of the composite roller in complex environments can be improved, making the quality of the composite roller significantly better than that of the prior art in specific environments.
[0039] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods. Those skilled in the art should also understand that the reaction time and drug feeding involved in this application cannot be absolutely accurate in the actual production process, but are all within the allowable error range. For example, if you expect to heat the sample for 30 minutes, the actual operation may be 1 second more or less than 1 second in 30 minutes; if you expect to weigh 30g of sample, you may actually weigh 30.001g or 29.998g.
[0040] Experimental Example 1 Wet Flue Gas Desulfurization Environment Simulation Experiment
[0041] This experimental example is intended to simulate a wet flue gas desulfurization environment, which usually significantly reduces the service life of the roller.
[0042] The temperature of the test chamber was controlled at 60±1℃, the humidity was 75%, and sulfur dioxide gas was added to make its content 1g / m 3 .
[0043] The samples to be tested are placed in the above-mentioned experimental box for 30 days.
[0044] Experimental Example 2: Room temperature placement experiment
[0045] The temperature of the experimental box was controlled at 25±1℃ and the humidity was 30%.
[0046] The samples to be tested are placed in the above-mentioned experimental box for 30 days.
[0047] Experimental Example 3 Flame retardant test experiment
[0048] The test is carried out in a combustion box. A 400cc alcohol torch is installed on the left inner side of the box, and a specimen clamp is installed on the right inner side to fix the specimen. The alcohol torch is tilted upwards at 45° and is equipped with an advance and retreat device. The test uses more than 95% industrial pure alcohol as fuel.
[0049] Experimental steps: Draw a mark on the wide surface of the sample at 25mm and 100mm away from the ignition source, then place the sample horizontally with its long axis, and fix it on the sample clamp at 45° with the axis of its cross section at the horizontal. Place a water tray 300mm below it. Light the alcohol burner, adjust the flame length to 25mm and turn it into a blue flame, and control the distance between the flame core and the lower edge of the sample to about 6mm. Start timing, and apply the flame for 30 seconds. Do not move the alcohol burner during this period. After the time is up, remove the flame to observe whether the sample has flame burning and keep a record. The same sample is considered qualified if it has no flame burning after repeated tests twice.
[0050] Experimental Example 4 Test method for antistatic ability
[0051] The equipment uses ZC46A high insulation resistance measuring instrument to measure the upper and lower surface resistance values of the sample.
[0052] Instrument structure: It mainly consists of five parts, such as Figure 1 shown.
[0053] (1) DC high voltage output: 10, 50, 100, 500, 1000V; (2) Select the appropriate range multiplier according to the resistance value and DC high voltage value of the sample; (3) High input impedance DC amplifier (input impedance > 1015 Ω); (4) Indicator, indicating the insulation resistance being measured; (5) The power supply supplies working power to each part of the instrument.
[0054] The main principle of the instrument when performing high resistance test is as follows Figure 2 As shown, during the test, the test sample resistance Rx is connected in series with the input resistance (multiplier resistance) Ro of the high impedance DC amplifier and connected across the DC power supply. The high impedance DC amplifier amplifies the divided voltage Uo on its input resistance Ro and sends it to the indicator to indicate the measured insulation resistance value, and calculates the insulation resistance according to formula (a).
[0055]
[0056] Among them, U represents the test voltage, Ro represents the rate sampling resistor, the voltage on it is Uo, Rx represents the insulation resistance of the sample being tested, and Ko represents the amplification factor of the amplifier.
[0057] Experimental Example 5 Wear resistance test
[0058] The Akron abrasion test is adopted, and its specific method can be referred to GB / T1689-2014.
[0059] The Akron wear loss of the material is expressed as a percentage of mass loss per unit travel (g / 1.61km) and is calculated according to formula (b)
[0060] Where x represents the mass loss percentage, M represents the mass loss (g / 1.61km), and M0 represents the initial mass of the tested sample.
[0061] Experimental Example 6 Experimental plan A
[0062] Weigh 10 parts of quartz sand, 6 parts of polypropylene, 1.25 parts of graphite, 0.5 parts of zinc borate, and 0.1 parts of molybdenum dioxide, and sieve the above raw materials before weighing to make the particle size of the raw materials no greater than 500 μm; Place the prepared raw materials into a blender and stir for 30 minutes to fully mix the raw materials; The components obtained in the previous step are placed into an extruder, which includes a feed inlet heating section, a feed zone heating section, a screw zone heating section, a barrel zone heating section and a die head heating section. The heating temperatures are 110°C, 140°C, 180°C, 220°C, and 210°C, respectively, and the heating times are 2 min, 3 min, 5 min, 3 min, and 2 min, respectively.
[0063] The components obtained in the previous step are placed in a pressing machine mold for pressing and molding to obtain a roller body.
[0064] Experimental plan B
[0065] Weigh 10 parts of quartz sand, 6 parts of polypropylene, 1.25 parts of graphite, 0.5 parts of zinc borate, 0.1 parts of molybdenum dioxide, and 0.12 parts of polytetrafluoroethylene, and sieve the above raw materials before weighing to make the particle size of the raw materials no greater than 500 μm; Place the prepared raw materials into a blender and stir for 30 minutes to fully mix the raw materials; The components obtained in the previous step are placed into an extruder, which includes a feed inlet heating section, a feed zone heating section, a screw zone heating section, a barrel zone heating section and a die head heating section. The heating temperatures are 110°C, 140°C, 180°C, 220°C, and 210°C, respectively, and the heating times are 2 min, 3 min, 5 min, 3 min, and 2 min, respectively.
[0066] The components obtained in the previous step are placed in a pressing machine mold for pressing and molding to obtain a roller body.
[0067] Experimental plan C
[0068] Weigh 10 parts of quartz sand, 6 parts of polypropylene, 1.25 parts of graphite, 0.5 parts of zinc borate, 0.1 parts of molybdenum dioxide, 0.12 parts of polytetrafluoroethylene, and 0.02 parts of sodium carboxymethyl cellulose, and sieve the above raw materials before weighing so that the particle size of the raw materials is not more than 500 μm; Place the prepared raw materials into a blender and stir for 30 minutes to fully mix the raw materials; The components obtained in the previous step are placed into an extruder, which includes a feed inlet heating section, a feed zone heating section, a screw zone heating section, a barrel zone heating section and a die head heating section. The heating temperatures are 110°C, 140°C, 180°C, 220°C, and 210°C, respectively, and the heating times are 2 min, 3 min, 5 min, 3 min, and 2 min, respectively.
[0069] The components obtained in the previous step are placed in a pressing machine mold for pressing and molding to obtain a roller body.
[0070] Experimental plan D
[0071] Weigh 10 parts of quartz sand, 6 parts of polypropylene, 1.25 parts of graphite, 0.5 parts of zinc borate, 0.1 parts of molybdenum dioxide, 0.12 parts of polytetrafluoroethylene, 0.03 parts of stearic acid, and 0.02 parts of sodium carboxymethyl cellulose, and sieve the above raw materials before weighing so that the particle size of the raw materials is not more than 500 μm; Place the prepared raw materials into a blender and stir for 30 minutes to fully mix the raw materials; The components obtained in the previous step are placed into an extruder, which includes a feed inlet heating section, a feed zone heating section, a screw zone heating section, a barrel zone heating section and a die head heating section. The heating temperatures are 110°C, 140°C, 180°C, 220°C, and 210°C, respectively, and the heating times are 2 min, 3 min, 5 min, 3 min, and 2 min, respectively.
[0072] The components obtained in the previous step are placed in a pressing machine mold for pressing and molding to obtain a roller body.
[0073] Experimental plan E
[0074] Weigh 10 parts of quartz sand, 6 parts of polypropylene, 1.25 parts of graphite, 0.5 parts of zinc borate, 0.1 parts of molybdenum dioxide, 0.12 parts of polytetrafluoroethylene, and 0.1 parts of silicon dioxide, and sieve the above raw materials before weighing so that the particle size of the raw materials is not more than 500 μm; Place the prepared raw materials into a blender and stir for 30 minutes to fully mix the raw materials; The components obtained in the previous step are placed into an extruder, which includes a feed inlet heating section, a feed zone heating section, a screw zone heating section, a barrel zone heating section and a die head heating section. The heating temperatures are 110°C, 140°C, 180°C, 220°C, and 210°C, respectively, and the heating times are 2 min, 3 min, 5 min, 3 min, and 2 min, respectively.
[0075] The components obtained in the previous step are placed in a pressing machine mold for pressing and molding to obtain a roller body.
[0076] Experimental Plan F Weigh 10 parts of quartz sand, 6 parts of polypropylene, 1.25 parts of graphite, 0.5 parts of zinc borate, 0.1 parts of molybdenum dioxide, 0.12 parts of polytetrafluoroethylene, 0.1 parts of silicon dioxide, 0.03 parts of stearic acid, and 0.02 parts of sodium carboxymethyl cellulose, and sieve the above raw materials before weighing so that the particle size of the raw materials is not more than 500 μm; Place the prepared raw materials into a blender and stir for 30 minutes to fully mix the raw materials; The components obtained in the previous step are placed into an extruder, which includes a feed inlet heating section, a feed zone heating section, a screw zone heating section, a barrel zone heating section and a die head heating section. The heating temperatures are 110°C, 140°C, 180°C, 220°C, and 210°C, respectively, and the heating times are 2 min, 3 min, 5 min, 3 min, and 2 min, respectively.
[0077] The components obtained in the previous step are placed in a pressing machine mold for pressing and molding to obtain a roller body.
[0078] Experimental plan G
[0079] Take 0.1 parts of sodium carboxymethyl cellulose and dissolve it in a proper amount of warm water, the temperature of which is 40°C, to obtain a sodium carboxymethyl cellulose solution. Weigh 0.6 parts of polytetrafluoroethylene and 0.15 parts of stearic acid, pass through a 16-mesh sieve, and place in a fluidized bed. The sodium carboxymethyl cellulose solution is sprayed to achieve material mixing in a fluidized bed; wherein the flow rate of the sodium carboxymethyl cellulose solution is 10 L / h, the air inlet temperature of the fluidized bed is 50°C, and the air inlet volume is 15 m 3 / h, atomization pressure is 1.0Bar; After spraying, the mixture was dried at 50°C for 30 min to obtain composite A particles. Screening the composite A with a particle size of 200-500 μm as a wear-resistant additive; Weigh 10 parts of quartz sand, 6 parts of polypropylene, 1.25 parts of graphite, 0.5 parts of zinc borate, 0.1 parts of molybdenum dioxide, and 0.17 parts of wear-resistant additives, and sieve the above raw materials before weighing so that the particle size of the raw materials is not more than 500 μm; Place the prepared raw materials into a blender and stir for 30 minutes to fully mix the raw materials; The components obtained in the previous step are placed into an extruder, which includes a feed inlet heating section, a feed zone heating section, a screw zone heating section, a barrel zone heating section and a die head heating section. The heating temperatures are 110°C, 140°C, 180°C, 220°C, and 210°C, respectively, and the heating times are 2 min, 3 min, 5 min, 3 min, and 2 min, respectively.
[0080] The components obtained in the previous step are placed in a pressing machine mold for pressing and molding to obtain a roller body.
[0081] Experimental plan H
[0082] Take 0.1 parts of sodium carboxymethyl cellulose and dissolve it in a proper amount of warm water, the temperature of which is 40°C, to obtain a sodium carboxymethyl cellulose solution. Weigh 0.6 parts of polytetrafluoroethylene, 0.15 parts of stearic acid, and 0.5 parts of silicon dioxide, pass through a 16-mesh sieve, and place in a fluidized bed. The sodium carboxymethyl cellulose solution is sprayed to achieve material mixing in a fluidized bed; wherein the flow rate of the sodium carboxymethyl cellulose solution is 10 L / h, the air inlet temperature of the fluidized bed is 50°C, and the air inlet volume is 15 m 3 / h, atomization pressure is 1.0Bar; After spraying, the mixture was dried at 50°C for 30 min to obtain composite A particles. Screening the composite A with a particle size of 200-500 μm as a wear-resistant additive; Weigh 10 parts of quartz sand, 6 parts of polypropylene, 1.25 parts of graphite, 0.5 parts of zinc borate, 0.1 parts of molybdenum dioxide, and 0.17 parts of wear-resistant additives, and sieve the above raw materials before weighing so that the particle size of the raw materials is not more than 500 μm; Place the prepared raw materials into a blender and stir for 30 minutes to fully mix the raw materials; The components obtained in the previous step are placed into an extruder, which includes a feed inlet heating section, a feed zone heating section, a screw zone heating section, a barrel zone heating section and a die head heating section. The heating temperatures are 110°C, 140°C, 180°C, 220°C, and 210°C, respectively, and the heating times are 2 min, 3 min, 5 min, 3 min, and 2 min, respectively.
[0083] The components obtained in the previous step are placed in a pressing machine mold for pressing and forming to obtain a roller body. Experimental Scheme I Referring to the preparation method of Example 1 in Chinese invention patent CN1310809C, a roller body is obtained.
[0084] The roller bodies obtained by Experimental Scheme AI were placed in the environments of Experimental Example 1 and Experimental Example 2 for 30 days, respectively, and the wear resistance of each scheme was measured according to the method of Experimental Example 5, as shown in Table 1.
[0085] Table 1 Wear resistance of experimental scheme AH under different environments Group Experimental Example 1 Environment (%) Experimental Example 2 Environment (%) Experimental plan A 1.08 0.60 Experimental plan B 1.10 0.58 Experimental plan C 1.04 0.61 Experimental plan D 0.92 0.55 Experimental plan E 1.02 0.52 Experimental Plan F 1.16 0.50 Experimental plan G 0.68 0.46 Experimental plan H 0.86 0.49 Experimental Protocol I 1.98 1.02
[0086] According to the experimental results in Table 1, the applicant can preliminarily deduce the following conclusions: First, referring to Experimental Scheme I, the roller body in the prior art will have a significant decrease in wear resistance under the environment of Experimental Example 1, indicating that the adaptability of the existing roller body in this environment is poor and needs to be improved urgently; Second, compared with Experimental Scheme I, Experimental Schemes AH provided in this application have better wear resistance properties regardless of the environment of Example 1 or Example 2; Third, by comparing experimental scheme D with experimental scheme AC, it can be seen that when the wear-resistant additives include polytetrafluoroethylene, stearic acid and sodium carboxymethyl cellulose at the same time, the wear-resistant properties of the roller body are more promoted; Fourth, by comparing Experimental Scheme D with Experimental Scheme EF, it can be seen that if the commonly used wear-resistant component silica is added to the wear-resistant additive, the wear resistance of the product cannot be improved under the environment of Experimental Example 1, and may even have an adverse effect. The applicant speculates that the environment may cause the denaturation of silica; Fifth, by comparing Experimental Scheme G with Experimental Scheme D, pre-preparing the wear-resistant additive through a fluidized bed can further improve its wear resistance under the environment of Experimental Example 1. The applicant speculates that the components can be fully mixed through the granulation process of the fluidized bed, and the sodium carboxymethyl cellulose can be wrapped to increase the wear resistance in acidic air. Example 1
[0087] Weigh 6 parts of quartz sand, 5 parts of polypropylene, 1 part of graphite, 0.2 parts of zinc borate, and 0.05 parts of molybdenum dioxide, and sieve the above raw materials before weighing to make the particle size of the raw materials no greater than 500 μm; Put the prepared raw materials into the blender and stir for 10 minutes to make the raw materials fully mixed; The components obtained in the previous step are placed into an extruder, which includes a feed inlet heating section, a feed zone heating section, a screw zone heating section, a barrel zone heating section and a die head heating section. The heating temperatures are 100°C, 120°C, 160°C, 200°C, and 180°C, respectively, and the heating times are 5min, 5min, 10min, 5min, and 5min, respectively.
[0088] The components obtained in the previous step are placed in a pressing machine mold for pressing and molding to obtain a roller body. Example 2
[0089] Weigh 10 parts of quartz sand, 6 parts of polypropylene, 1.25 parts of graphite, 0.5 parts of zinc borate, and 0.1 parts of molybdenum dioxide, and sieve the above raw materials before weighing to make the particle size of the raw materials no greater than 500 μm; Place the prepared raw materials into a blender and stir for 30 minutes to fully mix the raw materials; The components obtained in the previous step are placed into an extruder, which includes a feed inlet heating section, a feed zone heating section, a screw zone heating section, a barrel zone heating section and a die head heating section. The heating temperatures are 110°C, 140°C, 180°C, 220°C, and 210°C, respectively, and the heating times are 2 min, 3 min, 5 min, 3 min, and 2 min, respectively.
[0090] The components obtained in the previous step are placed in a pressing machine mold for pressing and molding to obtain a roller body. Example 3
[0091] Weigh 20 parts of quartz sand, 10 parts of polypropylene, 3 parts of graphite, 2 parts of zinc borate, and 0.2 parts of molybdenum dioxide, and sieve the above raw materials before weighing to make the particle size of the raw materials no greater than 500 μm; Place the prepared raw materials into a blender and stir for 60 minutes to fully mix the raw materials; The components obtained in the previous step are placed into an extruder, which includes a feed inlet heating section, a feed zone heating section, a screw zone heating section, a barrel zone heating section and a die head heating section. The heating temperatures are 120°C, 160°C, 200°C, 240°C, and 240°C, respectively, and the heating times are 2min, 2min, 2min, 2min, and 2min, respectively.
[0092] The components obtained in the previous step are placed in a pressing machine mold for pressing and molding to obtain a roller body. Example 4
[0093] Weigh 6 parts of quartz sand, 5 parts of polypropylene, 1 part of graphite, 0.2 parts of zinc borate, 0.05 parts of molybdenum dioxide, 0.05 parts of polytetrafluoroethylene, 0.02 parts of stearic acid, and 0.01 parts of sodium carboxymethyl cellulose, and sieve the above raw materials before weighing so that the particle size of the raw materials is not more than 500 μm; Put the prepared raw materials into the blender and stir for 10 minutes to make the raw materials fully mixed; The components obtained in the previous step are placed into an extruder, which includes a feed inlet heating section, a feed zone heating section, a screw zone heating section, a barrel zone heating section and a die head heating section. The heating temperatures are 100°C, 120°C, 160°C, 200°C, and 180°C, respectively, and the heating times are 5min, 5min, 10min, 5min, and 5min, respectively.
[0094] The components obtained in the previous step are placed in a pressing machine mold for pressing and molding to obtain a roller body. Example 5
[0095] Weigh 10 parts of quartz sand, 6 parts of polypropylene, 1.25 parts of graphite, 0.5 parts of zinc borate, 0.1 parts of molybdenum dioxide, 0.12 parts of polytetrafluoroethylene, 0.03 parts of stearic acid, and 0.02 parts of sodium carboxymethyl cellulose, and sieve the above raw materials before weighing so that the particle size of the raw materials is not more than 500 μm; Place the prepared raw materials into a blender and stir for 30 minutes to fully mix the raw materials; The components obtained in the previous step are placed into an extruder, which includes a feed inlet heating section, a feed zone heating section, a screw zone heating section, a barrel zone heating section and a die head heating section. The heating temperatures are 110°C, 140°C, 180°C, 220°C, and 210°C, respectively, and the heating times are 2 min, 3 min, 5 min, 3 min, and 2 min, respectively.
[0096] The components obtained in the previous step are placed in a pressing machine mold for pressing and molding to obtain a roller body.
[0097] Example 6 Weigh 20 parts of quartz sand, 10 parts of polypropylene, 3 parts of graphite, 2 parts of zinc borate, 0.2 parts of molybdenum dioxide, 0.4 parts of polytetrafluoroethylene, 0.05 parts of stearic acid, and 0.05 parts of sodium carboxymethyl cellulose, and sieve the above raw materials before weighing so that the particle size of the raw materials is not more than 500 μm; Place the prepared raw materials into a blender and stir for 60 minutes to fully mix the raw materials; The components obtained in the previous step are placed into an extruder, which includes a feed inlet heating section, a feed zone heating section, a screw zone heating section, a barrel zone heating section and a die head heating section. The heating temperatures are 120°C, 160°C, 200°C, 240°C, and 240°C, respectively, and the heating times are 2min, 2min, 2min, 2min, and 2min, respectively.
[0098] The components obtained in the previous step are placed in a pressing machine mold for pressing and molding to obtain a roller body. Example 7
[0099] Take 0.1 parts of sodium carboxymethyl cellulose and dissolve it in a proper amount of warm water, the temperature of which is 40°C, to obtain a sodium carboxymethyl cellulose solution. Weigh 0.6 parts of polytetrafluoroethylene and 0.15 parts of stearic acid, pass through a 16-mesh sieve, and place in a fluidized bed. The sodium carboxymethyl cellulose solution is sprayed to achieve material mixing in a fluidized bed; wherein the flow rate of the sodium carboxymethyl cellulose solution is 5 L / h, the inlet air temperature of the fluidized bed is 45°C, and the inlet air volume is 10 m 3 / h, atomization pressure is 0.5Bar; After spraying, the mixture was dried at 40°C for 40 min to obtain composite A particles. Screening the composite A with a particle size of 200-500 μm as a wear-resistant additive; Weigh 6 parts of quartz sand, 5 parts of polypropylene, 1 part of graphite, 0.2 parts of zinc borate, 0.05 parts of molybdenum dioxide, and 0.08 parts of wear-resistant additives, and sieve the above raw materials before weighing to make the particle size of the raw materials no greater than 500 μm; Put the prepared raw materials into the blender and stir for 10 minutes to make the raw materials fully mixed; The components obtained in the previous step are placed into an extruder, which includes a feed inlet heating section, a feed zone heating section, a screw zone heating section, a barrel zone heating section and a die head heating section. The heating temperatures are 100°C, 120°C, 160°C, 200°C, and 180°C, respectively, and the heating times are 5min, 5min, 10min, 5min, and 5min, respectively.
[0100] The components obtained in the previous step are placed in a pressing machine mold for pressing and molding to obtain a roller body. Example 8
[0101] Take 0.1 parts of sodium carboxymethyl cellulose and dissolve it in a proper amount of warm water, the temperature of which is 40°C, to obtain a sodium carboxymethyl cellulose solution. Weigh 0.6 parts of polytetrafluoroethylene and 0.15 parts of stearic acid, pass through a 16-mesh sieve, and place in a fluidized bed. The sodium carboxymethyl cellulose solution is sprayed to achieve material mixing in a fluidized bed; wherein the flow rate of the sodium carboxymethyl cellulose solution is 10 L / h, the air inlet temperature of the fluidized bed is 50°C, and the air inlet volume is 15 m 3 / h, atomization pressure is 1.0Bar; After spraying, the mixture was dried at 50°C for 30 min to obtain composite A particles. Screening the composite A with a particle size of 200-500 μm as a wear-resistant additive; Weigh 10 parts of quartz sand, 6 parts of polypropylene, 1.25 parts of graphite, 0.5 parts of zinc borate, 0.1 parts of molybdenum dioxide, and 0.17 parts of wear-resistant additives, and sieve the above raw materials before weighing so that the particle size of the raw materials is not more than 500 μm; Place the prepared raw materials into a blender and stir for 30 minutes to fully mix the raw materials; The components obtained in the previous step are placed into an extruder, which includes a feed inlet heating section, a feed zone heating section, a screw zone heating section, a barrel zone heating section and a die head heating section. The heating temperatures are 110°C, 140°C, 180°C, 220°C, and 210°C, respectively, and the heating times are 2 min, 3 min, 5 min, 3 min, and 2 min, respectively.
[0102] The components obtained in the previous step are placed in a pressing machine mold for pressing and molding to obtain a roller body. Example 9
[0103] Take 0.1 parts of sodium carboxymethyl cellulose and dissolve it in a proper amount of warm water, the temperature of which is 40°C, to obtain a sodium carboxymethyl cellulose solution. Weigh 0.6 parts of polytetrafluoroethylene and 0.15 parts of stearic acid, pass through a 16-mesh sieve, and place in a fluidized bed. The sodium carboxymethyl cellulose solution is sprayed to achieve material mixing in a fluidized bed; wherein the flow rate of the sodium carboxymethyl cellulose solution is 20 L / h, the inlet air temperature of the fluidized bed is 55°C, and the inlet air volume is 20 m 3 / h, atomization pressure is 1.5Bar; After spraying, the mixture was dried at 55°C for 10 min to obtain composite A particles. Screening the composite A with a particle size of 200-500 μm as a wear-resistant additive; Weigh 20 parts of quartz sand, 10 parts of polypropylene, 3 parts of graphite, 2 parts of zinc borate, 0.2 parts of molybdenum dioxide, and 0.5 parts of wear-resistant additive, and sieve the above raw materials before weighing so that the particle size of the raw materials is not more than 500 μm; Place the prepared raw materials into a blender and stir for 60 minutes to fully mix the raw materials; The components obtained in the previous step are placed into an extruder, which includes a feed inlet heating section, a feed zone heating section, a screw zone heating section, a barrel zone heating section and a die head heating section. The heating temperatures are 120°C, 160°C, 200°C, 240°C, and 240°C, respectively, and the heating times are 2min, 2min, 2min, 2min, and 2min, respectively.
[0104] The components obtained in the previous step are placed in a pressing machine mold for pressing and molding to obtain a roller body.
[0105] Example 10 This embodiment is basically the same as Embodiment 8, except that: When placing the raw materials into the blender, 0.01 parts of polyethylene glycol 8000 were added. Embodiment 11
[0106] This embodiment is basically the same as Embodiment 8, except that: When placing the raw materials into the blender, add 0.05 parts of polyethylene glycol 8000. Example 12
[0107] This embodiment is basically the same as Embodiment 8, except that: When placing the raw materials into the blender, add 0.1 parts of polyethylene glycol 8000. Example 13
[0108] This embodiment is basically the same as Embodiment 8, except that: The flame retardant zinc borate was replaced by aluminum hypophosphite. Embodiment 14
[0109] This embodiment is basically the same as Embodiment 8, except that: In the step of weighing the raw materials, carbon black is added, specifically: Weigh 10 parts of quartz sand, 6 parts of polypropylene, 1.25 parts of graphite, 0.5 parts of carbon black, 0.5 parts of zinc borate, 0.1 parts of molybdenum dioxide, and 0.17 parts of wear-resistant additives. Before weighing, sieve the above raw materials respectively to make the particle size of the raw materials not greater than 500 μm. Embodiment 15
[0110] This embodiment is basically the same as Embodiment 8, except that: In the step of weighing the raw materials, carbon black is added, specifically: Weigh 10 parts of quartz sand, 6 parts of polypropylene, 1.25 parts of graphite, 2 parts of carbon black, 0.5 parts of zinc borate, 0.1 parts of molybdenum dioxide, and 0.17 parts of wear-resistant additives. Before weighing, sieve the above raw materials respectively to make the particle size of the raw materials not greater than 500 μm.
[0111] Comparative Example 1
[0112] The roller body was obtained by referring to the preparation method of Example 1 in Chinese invention patent CN1310809C.
[0113] Comparative Example 2
[0114] Take 0.1 parts of sodium carboxymethyl cellulose and dissolve it in a proper amount of warm water, the temperature of which is 40°C, to obtain a sodium carboxymethyl cellulose solution. Weigh 0.6 parts of polytetrafluoroethylene, 0.15 parts of stearic acid, and 0.5 parts of silicon dioxide, pass through a 16-mesh sieve, and place in a fluidized bed. The sodium carboxymethyl cellulose solution is sprayed to achieve material mixing in a fluidized bed; wherein the flow rate of the sodium carboxymethyl cellulose solution is 10 L / h, the air inlet temperature of the fluidized bed is 50°C, and the air inlet volume is 15 m 3 / h, atomization pressure is 1.0Bar; After spraying, the mixture was dried at 50°C for 30 min to obtain composite A particles. Screening the composite A with a particle size of 200-500 μm as a wear-resistant additive; Weigh 10 parts of quartz sand, 6 parts of polypropylene, 1.25 parts of graphite, 0.5 parts of zinc borate, 0.1 parts of molybdenum dioxide, and 0.17 parts of wear-resistant additives, and sieve the above raw materials before weighing so that the particle size of the raw materials is not more than 500 μm; Place the prepared raw materials into a blender and stir for 30 minutes to fully mix the raw materials; The components obtained in the previous step are placed into an extruder, which includes a feed inlet heating section, a feed zone heating section, a screw zone heating section, a barrel zone heating section and a die head heating section. The heating temperatures are 110°C, 140°C, 180°C, 220°C, and 210°C, respectively, and the heating times are 2 min, 3 min, 5 min, 3 min, and 2 min, respectively.
[0115] The components obtained in the previous step are placed in a pressing machine mold for pressing and molding to obtain a roller body.
[0116] Comparative Example 3
[0117] This comparative example is basically the same as comparative example 2, except that: The silica was adjusted to 0.01 parts.
[0118] Comparative Example 4
[0119] This comparative example is substantially the same as Example 8, except that: Screening the composite A with a particle size of 500-1000 μm as a wear-resistant additive; Weigh 10 parts of quartz sand, 6 parts of polypropylene, 1.25 parts of graphite, 0.5 parts of zinc borate, 0.1 parts of molybdenum dioxide, and 0.17 parts of wear-resistant additive, and sieve the above raw materials respectively to make the raw material particle size 500-1000 μm.
[0120] Comparative Example 5
[0121] Commercially available rubber rollers. Example 16
[0122] The roller bodies prepared according to the methods of Examples 1-15 and Comparative Examples 1-5 were tested for flame retardancy, antistatic ability, and wear resistance using the methods of Experimental Examples 3-5. The test results are shown in Table 2.
[0123] Table 2 Flame retardancy, antistatic ability and wear resistance of the roller bodies in Examples 1-15 and Comparative Examples 1-5 Group Flame retardant ability Average surface resistance (Ω) Average resistance of lower surface (Ω) Wear resistance (%) Example 1 qualified <![CDATA[4.6×10 5 ]]> <![CDATA[5.6×10 6 ]]> 0.59 Example 2 qualified <![CDATA[4.8×10 5 ]]> <![CDATA[5.7×10 6 ]]> 0.61 Example 3 qualified <![CDATA[5.2×10 5 ]]> <![CDATA[6.4×10 6 ]]> 0.59 Example 4 qualified <![CDATA[5.4×10 5 ]]> <![CDATA[6.4×10 6 ]]> 0.55 Example 5 qualified <![CDATA[6.0×10 5 ]]> <![CDATA[7.1×10 6 ]]> 0.57 Example 6 qualified <![CDATA[6.0×10 5 ]]> <![CDATA[6.9×10 6 ]]> 0.54 Example 7 qualified <![CDATA[5.8×10 5 ]]> <![CDATA[6.8×10 6 ]]> 0.51 Example 8 qualified <![CDATA[5.2×10 5 ]]> <![CDATA[6.0×10 6 ]]> 0.50 Example 9 qualified <![CDATA[5.3×10 5 ]]> <![CDATA[6.0×10 6 ]]> 0.52 Example 10 qualified <![CDATA[5.0×10 5 ]]> <![CDATA[5.5×10 6 ]]> 0.52 Embodiment 11 qualified <![CDATA[4.6×10 5 ]]> <![CDATA[5.6×10 6 ]]> 0.51 Example 12 qualified <![CDATA[4.8×10 5 ]]> <![CDATA[5.7×10 6 ]]> 0.51 Example 13 qualified <![CDATA[6.2×10 5 ]]> <![CDATA[7.1×10 6 ]]> 0.51 Embodiment 14 qualified <![CDATA[5.1×10 5 ]]> <![CDATA[6.2×10 6 ]]> 0.48 Embodiment 15 qualified <![CDATA[4.9×10 5 ]]> <![CDATA[5.7×10 6 ]]> 0.46 Comparative Example 1 qualified <![CDATA[8.6×10 5 ]]> <![CDATA[9.8×10 6 ]]> 0.67 Comparative Example 2 qualified <![CDATA[5.0×10 5 ]]> <![CDATA[5.9×10 6 ]]> 0.50 Comparative Example 3 qualified <![CDATA[5.1×10 5 ]]> <![CDATA[6.4×10 6 ]]> 0.52 Comparative Example 4 qualified <![CDATA[5.5×10 5 ]]> <![CDATA[6.6×10 6 ]]> 0.60 Comparative Example 5 qualified <![CDATA[6.1×10 5 ]]> <![CDATA[6.7×10 6 ]]> 1.08 According to the results in Table 2, we can see that: First, the flame retardancy, resistance value, and wear resistance of each embodiment proposed in the present application are all qualified indicators, and the antistatic effect and wear resistance are better than those of the prior art (Comparative Example 1); at the same time, the wear resistance is also significantly better than that of the commercially available rubber roller (Comparative Example 5); Second, by comparing Example 8 with Example 2, the wear-resistant additive proposed in this application can improve the life of the product in a harsh environment, but its antistatic ability is reduced; further comparing Examples 10-12 with Example 8, adding a small amount of polyethylene glycol 8000 component to the component can improve the antistatic effect of this product to a certain extent; Third, by comparing Examples 14-15 with Example 8, adding a small amount of carbon black to the components of the present application can improve the antistatic ability of the product to a certain extent.
[0124] Embodiment 17
[0125] The roller bodies prepared according to the methods of Examples 1-15 and Comparative Examples 1-5 were placed using the method of Experimental Example 1, and then tested for flame retardancy, antistatic ability, and wear resistance using the methods of Experimental Examples 3-5. The test results are shown in Table 3.
[0126] Table 3 Flame retardancy, antistatic ability and wear resistance of the roller bodies in Examples 1-15 and Comparative Examples 1-4 Group Flame retardant ability Average surface resistance (Ω) Average resistance of lower surface (Ω) Wear resistance (%) Example 1 qualified <![CDATA[4.8×10 5 ]]> <![CDATA[5.9×10 6 ]]> 1.10 Example 2 qualified <![CDATA[4.8×10 5 ]]> <![CDATA[5.8×10 6 ]]> 1.08 Example 3 qualified <![CDATA[5.6×10 5 ]]> <![CDATA[6.3×10 6 ]]> 1.14 Example 4 qualified <![CDATA[5.9×10 5 ]]> <![CDATA[6.7×10 6 ]]> 0.90 Example 5 qualified <![CDATA[6.6×10 5 ]]> <![CDATA[7.5×10 6 ]]> 0.92 Example 6 qualified <![CDATA[6.3×10 5 ]]> <![CDATA[7.0×10 6 ]]> 0.89 Example 7 qualified <![CDATA[5.8×10 5 ]]> <![CDATA[6.7×10 6 ]]> 0.70 Example 8 qualified <![CDATA[6.3×10 5 ]]> <![CDATA[7.3×10 6 ]]> 0.68 Example 9 qualified <![CDATA[7.0×10 5 ]]> <![CDATA[8.1×10 6 ]]> 0.65 Example 10 qualified <![CDATA[5.4×10 5 ]]> <![CDATA[6.5×10 6 ]]> 0.68 Embodiment 11 qualified <![CDATA[5.0×10 5 ]]> <![CDATA[6.2×10 6 ]]> 0.65 Example 12 qualified <![CDATA[5.1×10 5 ]]> <![CDATA[6.4×10 6 ]]> 0.69 Example 13 qualified <![CDATA[5.2×10 5 ]]> <![CDATA[6.1×10 6 ]]> 0.73 Embodiment 14 qualified <![CDATA[6.4×10 5 ]]> <![CDATA[7.1×10 6 ]]> 0.71 Embodiment 15 qualified <![CDATA[6.6×10 5 ]]> <![CDATA[7.4×10 6 ]]> 0.70 Comparative Example 1 qualified <![CDATA[9.3×10 5 ]]> <![CDATA[10.1×10 6 ]]> 1.97 Comparative Example 2 qualified <![CDATA[6.0×10 5 ]]> <![CDATA[6.9×10 6 ]]> 0.85 Comparative Example 3 qualified <![CDATA[6.9×10 5 ]]> <![CDATA[8.3×10 6 ]]> 0.78 Comparative Example 4 qualified <![CDATA[6.4×10 5 ]]> <![CDATA[7.6×10 6 ]]> 0.98 Comparative Example 5 qualified <![CDATA[6.7×10 5 ]]> <![CDATA[7.7×10 6 ]]> 1.66 According to the results in Table 3: First, the flame retardancy, resistance value, and wear resistance of each embodiment proposed in the present application are relatively stable in the high humidity and high sulfur environment of Experimental Example 1, and have significant advantages in wear resistance compared with the prior art (Comparative Example 1, Comparative Example 5); Second, by comparing Examples 4-9 with Examples 1-3, the wear-resistant additives proposed in this application can improve the life of the product in harsh environments, but their antistatic ability is reduced; further comparing Examples 10-12 with Example 8, adding a small amount of polyethylene glycol 8000 to the components can improve the antistatic effect of the product to a certain extent, and the impact in a high humidity and high sulfur environment is also small; Third, by comparing Example 8 with Comparative Example 2, after adding silica to the components, the wear resistance of the product in a high humidity and high sulfur environment is easily affected; referring to Comparative Example 2 and Comparative Example 3, when a small amount of silica is added, the wear resistance is slightly affected; Fourth, by comparing Example 8 with Comparative Example 4, the raw material particle size control in the present application also has a beneficial effect on the antistatic effect and wear resistance of the product in a high-humidity and high-sulfur environment.
[0127] Embodiment 18
[0128] The roller bodies obtained in Example 8 and Comparative Example 5 were respectively applied to the Guizhou Tangzhai Power Plant of the State Power Corporation, whose working environment includes wet flue gas desulfurization, and were operated internally in the on-site conveyor belt system for 6 months.
[0129] The roller body of Comparative Example 5 has been obviously worn after being used for 6 months, while the roller body of Example 8 is still intact and can be used normally.
[0130] Embodiment 19
[0131] In some embodiments of the present application, Figure 3 As shown, a composite roller is provided, and the composite roller is applied to a conveyor belt system, comprising: A connecting shaft 10, both ends of which are connected to mounting plates (not shown) of the conveyor belt system; The bearing seats 20 are sleeved on both ends of the connecting shaft 10; The bearing 30 is disposed in the bearing seat 20 and can rotate relative to the connecting shaft 10; A sealing structure 40 is disposed in the bearing seat 20 and performs a sealing function on the bearing 30; The roller body 50 is sleeved on the outside of the bearing seat 20, and its surface is in contact with the conveyor belt (not shown) for supporting the conveyor belt.
[0132] The composite roller obtained in the embodiment of the present application has the following properties: First, longer service life: under the same industrial and mining conditions, it is more than 5 times that of ordinary steel rollers and more than 2-3 times that of ordinary non-metallic rollers; at the same time, it also has good corrosion resistance in complex working environments. Second, high wear resistance: with the help of quartz sand, polypropylene, graphite and other components, the wear resistance and impact resistance of the composite graphene roller are significantly improved, greatly extending the service life of the roller. Third, impact resistance: the composite roller provided by the present application has excellent impact resistance and can be used directly at the coal drop point or impact point of the belt, solving the problem of non-metallic rollers being fragile in the prior art. Fourth, light weight: it is 1 / 3 of the weight of ordinary steel rollers, which is easy to install and maintain, and significantly reduces the labor intensity of workers. Fifth, zero damage to the belt: it has good self-lubrication, the roller surface does not scale or stab, reduces belt loss, and extends the service life of the belt. Sixth, low noise: less than 75 decibels when working, significantly reduces noise, and improves the noise working environment caused by the belt. Seventh, energy saving and power saving: due to the small running resistance, the power output of the belt conveyor can be reduced, thereby saving electricity. Eighth, stable, durable and maintenance-free: maintenance-free design, can be used for a long time after one installation.
[0133] In summary, the composite roller and the preparation method thereof provided in the embodiments of the present invention improve the wear resistance of the composite roller in complex environments by setting the components of the roller body to quartz sand, polypropylene, graphite and other components, solve the technical problem of the narrow application range of rollers in the prior art, achieve a better service life in specific harsh environments, and have good commercial prospects.
[0134] It should be pointed out that for ordinary technicians in this field, the technical features in the above embodiments can be freely combined, and the formed technical solutions also belong to the embodiments disclosed in this application.
[0135] Furthermore, without departing from the principles of the present application, several improvements and modifications may be made to the present application, and these improvements and modifications also fall within the protection scope of the claims of the present application.
Claims
1. A composite roller, characterized in that: include: The connecting shaft has two ends connected to the mounting plate. The bearing seat is mounted on both ends of the connecting shaft. A bearing is disposed in the bearing seat and is capable of rotating relative to the connecting shaft. The sealing structure is arranged in the bearing seat and seals the bearing. The roller body is sleeved outside the bearing seat, and its surface is in contact with the conveyor belt, and is used to support the conveyor belt; Wherein, the roller body comprises the following components: 6-20 parts of quartz sand, Polypropylene 5-10 parts, 1-3 parts of graphite.
2. The composite roller according to claim 1, characterized in that: The roller body further comprises: Wear-resistant additive 0.08-0.5 parts, The wear-resistant additives include: The mass ratio of polytetrafluoroethylene, stearic acid and sodium carboxymethyl cellulose is 5-8:1-2:
1.
3. The composite roller according to claim 2, characterized in that: The preparation method of the wear-resistant additive comprises the steps of: Take the indicated amount of sodium carboxymethyl cellulose and dissolve it in an appropriate amount of warm water, the temperature of which is 30-50°C, to obtain a sodium carboxymethyl cellulose solution. Take polytetrafluoroethylene and stearic acid and place them in a fluidized bed. The sodium carboxymethyl cellulose solution is sprayed to achieve material mixing in a fluidized bed; wherein the flow rate of the sodium carboxymethyl cellulose solution is 5-20 L / h, the air inlet temperature of the fluidized bed is 45-55°C, and the air inlet volume is 10-20 m 3 / h, atomization pressure is 0.5-1.5Bar; After spraying, the particles are dried at 40-55°C for 10-40 minutes to obtain composite A particles.
4. The composite roller according to claim 3, characterized in that: The composite A with a particle size of 200-500 μm was screened as a wear-resistant additive.
5. The composite roller according to any one of claims 1 to 4, characterized in that: The roller body further comprises: Flame retardant 0.2-2 parts, The flame retardant is selected from boron flame retardant or phosphorus flame retardant.
6. The composite roller according to claim 5, characterized in that: The boron flame retardant is zinc borate, and the phosphorus flame retardant is aluminum hypophosphite.
7. The composite roller according to any one of claims 1 to 4, characterized in that: The roller body further comprises: Lubricant 0.05-0.2 parts, The lubricant is selected from paraffin or molybdenum disulfide.
8. A method for preparing a composite roller, characterized in that: Includes steps: Prepare the raw materials for the rollers, Preparation of roller bodies, Assemble and form, The step of preparing the roller body specifically includes: Stir the raw materials. Put the prepared raw materials into the blender and stir for 10-60 minutes. Raw material extrusion, the components obtained in the raw material mixing step are placed into the extruder, heated at 100-240°C for 10-30 minutes, Compression molding: placing the components obtained in the raw material extrusion step into a compression mold of a compression machine for compression molding.
9. The preparation method according to claim 8, characterized in that: The preparation of raw materials for the roller comprises the following steps: The raw materials were sieved to make the particle size no greater than 500 μm.
10. The preparation method according to claim 8, characterized in that: The extruder comprises a feed port heating section, a feed zone heating section, a screw zone heating section, a barrel zone heating section and a die head heating section, the heating temperatures are 100-120°C, 120-160°C, 160-200°C, 200-240°C, 240-180°C respectively, and the heating times are 2-5min, 2-5min, 2-10min, 2-5min, 2-5min respectively.
Citation Information
Patent Citations
Belt conveyor for coal mine
CN118850626A
Compound material support roller and preparation method thereof
CN1310809C
Medicine granule, preparation method thereof, and preparation containing same
CN101548953A
Water-soluble anti-fingerprint surface treating agent for galvanized steel sheet and preparation method of surface treating agent
CN104356789A
Nano calcium carbonate modified polytetrafluoroethylene composite material for sealing valve
CN104592694A